Socio-cultural beliefs influence feeding practices of mothers and their children in Grand Popo, Benin - Yrence Urielle Amoussou Lokossou; Ayuk Betrand Tambe; Colette Azandjèmè; Xikombiso Mbhenyane (BMC, 2021)
Abstract Background Malnutrition is a major public health problem. It contributes to the high death rate among children in developing countries despite the various advocacies of institutions such as WHO and FAO and many other organisations. More research needs to be done in order to contribute to the achievement of the Sustainable Development Goals. The aim of this study was to explore socio-cultural practices and their influence on feeding practices of mothers and their children in Grand Popo, Benin. Methods A qualitative research methodology was used with an inductive approach. A pretested discussion guide was used to conduct focus group discussions with participants in their local language. Four focus group discussions were held in 4 villages located in both the rural and the semi-urban areas with each focus group comprising seven to eight participants. The study protocol was approved by the Health Research Ethics Committee of Stellenbosch University. Focus group discussions were recorded, transcribed and translated to English. The data was analysed following the Creswell data analysis steps. Results All the children were breastfed, and 56.1% of children under 6 months received breast milk exclusively. Children were introduced to family foods at 5 months with very low consumption of animal protein and fruits. Mothers and children had monotonous diets with high consumption of vegetables and maize-based meals. Food taboos, particularly during pregnancy, were revealed. Those cultural beliefs were still followed by some mothers, and food rich in nutrients were pushed aside. Conclusions There is a need for educational interventions to raise awareness of the negative impacts of some socio-cultural practices on the health of the mother and child.